Pola Asuh Demokratis dan Penerapannya pada Anak Usia 5-6 Tahun dalam Perspektif Ibu di Desa Kembaran Kecamatan Purwokerto Timur Kabupaten Banyumas - Apri Nur Faizal, Andika (Program Studi Pendidikan Guru PAUD FKIP Universitas Mulawarman, 2025)
Democratic parenting is one of the parenting styles that provides children with broad opportunities for expression and exploration. Parents serve as the central figures in its implementation, with mothers playing a dominant role due to fathers’ work responsibilities. This parenting style emphasizes open communication, freedom for children to express opinions, and the establishment of clear rules to foster discipline. This study employs a qualitative case study method to describe findings collected through interviews and observations involving mothers and children in Kembaran Village. The results indicate that mothers apply democratic parenting adaptively, based on their children’s developmental needs. Key influencing factors include understanding the child’s character, the involvement of fathers, and age-appropriate adjustments. The implementation of democratic parenting positively affects children’s social and emotional development and helps prevent psychological cases of fatherlessness and motherlessness. This research is expected to contribute as an academic reference in parenting studies, supporting holistic growth and development in early childhood.